Social complexity as a driving force of gut microbiota exchange among conspecific hosts in non-human primates - Pinacho-Guendulain, Braulio; Montiel-Castro, Augusto Jacobo; Ramos-Fernández, Gabriel; Pacheco-López, Gustavo (Frontiers in Integrative Neuroscience, 2022)
The emergent concept of the social microbiome (Sarkar et al. 2020) implies a view of a highly connected biological world, in which microbial interchange across organisms may be influenced by social and ecological connections occurring at different levels of biological organization. We explore this idea reviewing evidence that suggest whether increasing social complexity in primate societies is associated with both higher diversity and greater similarity in the composition of the gut microbiota. By proposing a series of predictions regarding such relationship, we suggest the implications of a link between gut microbiota and primate social behavior. Overall, we find that enough empirical evidence already supports these predictions. Nonetheless, we conclude that studies with the necessary, sufficient, explicit, and available evidence are still scarce. Therefore, we propose the utility of founding future analyses on the utility of social complexity as a theoretical framework.